Antibacterial Activity of Ethyl Acetat Fraction of Basil Leave (Ocimum Basilicum L) Toward Escherichia Coli Growth - Marfuati, Sri; Weni, Mustika; Putri, Inayati Diana (Universitas Djuanda, 2024)
Antibiotic resistance to Escherichia coli is commonly found. Several studies have found that basil leaves contain chemical compounds: flavonoids, alkaloids, tannins, and saponins, which act as antibacterials. This research aimed to determine the inhibitory power of the ethyl acetate fraction of basil leaves (Ocimum basilicum L) on the growth of Escherichia coli. This study used a post-test-only control group design. This study contained five groups: one positive control group, one negative control group, and three treatment groups. The treatment group consisted of the ethyl acetate fraction of basil leaves at 12.5% μ, 25% μ, and 50% μ. The control group was a positive control K(+) with co-trimoxazole and a negative control K(-) with 10% Dimethyl Sulfoxide (DMSO). Kruskal walls test was chosen, followed by the Mann-Whitney difference test. In the Kruskal Walls test, a significant difference was found (p-value < 0.050) for basil leaf ethyl acetate fraction treatment. The largest average was obtained, namely the ethyl acetate fraction with a concentration of 12.5%. The Mann-Whitney test was carried out to determine fundamental differences between groups. The results of ethyl acetate fraction showed that the Minimum inhibitory concentration (MIC) for Escherichia coli was 12.5%.